Occupational Musculoskeletal Disorders. - Hadler, Nortin M. (Wolters Kluwer Health, 2004)
This standard-setting book is known for its practical approach to the assessment, management, and counseling of patients with regional musculoskeletal disorders resulting in occupational incapacity. The approach is supported by a display of the relevant science and the author's philosophy in approaching uncertainties and discrepancies. The Third Edition offers discussions of the current approach to the diagnosis and management of fibromyalgia and its sister functional somatic syndromes. Recent scientific studies explore the treatment of regional musculoskeletal disorders when such a sufferer f.